2021
DOI: 10.1101/2021.02.04.21251127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Transmission Risk from sports Equipment (STRIKE)

Abstract: OBJECTIVES: To investigate the potential of shared sporting equipment as transmission vectors of SARS-CoV-2 during the reintroduction of sports such as soccer, rugby, cricket, tennis, golf and gymnastics. SETTING: Laboratory based live SARS-CoV-2 virus study. INTERVENTIONS: Ten different types of sporting equipment were inoculated with 40μl droplets containing clinically relevant high and low concentrations of live SARS-CoV-2 virus. Materials were then swabbed at time points relevant to sports (1, 5, 15, 30, 9… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“… 15 These findings may not be directly applicable to golf given the indoor, high-intensity nature of squash. Previous literature has reported the rate of viral recovery from contaminated sports equipment to be low, 16 and we did not associate any positive cases with fomite transmission via golfing equipment.…”
Section: Resultssupporting
(Expert classified)
“… 15 These findings may not be directly applicable to golf given the indoor, high-intensity nature of squash. Previous literature has reported the rate of viral recovery from contaminated sports equipment to be low, 16 and we did not associate any positive cases with fomite transmission via golfing equipment.…”
Section: Resultssupporting
(Expert classified)
“…50 Golf is an equipment-based sports and there may be concerns regarding the risk of transmission via fomites on equipment. However, Edwards et al 51 showed that only 0.74% of COVID-19 virus was recoverable at 1 min in high inoculum when applied to a variety of sporting equipment (including a golf ball). Unpublished data from 32 professional golf events on the European Tour, Ladies European Tour and Challenge Tour which regularly tested participants found no transmission from golfer to golfer in outdoor environments.…”
Section: Benefits Of Golf During Covid-19 and For Rehabilitation From Illnessmentioning
confidence: 99%
“…These sources suggest that it is plausible but less likely that a viral reservoir would persist into consecutive game weeks. Conversely two studies [38,40] suggest much shorter persistence time in the order of minutes and maybe a few hours dependent on the surface type. This disagreement could be indicative of differing methods.…”
Section: Properties Of Coronavirusesmentioning
confidence: 96%
“…Edwards et al [40] conducted perhaps the most complete sports equipment study to date. They inoculated 10 different items of sporting equipment with SARS-CoV-2 virus of concentrations 5.4 × 10 4 and 5.4 × 102 PFU, testing each for virus at 1, 5, 15, 30 and 90 minutes.…”
Section: Properties Of Coronavirusesmentioning
confidence: 99%
See 1 more Smart Citation